Social participation of community-dwelling older adults in western China: A latent profile analysis - Di Luo; Shiqi Yu; Jun Wang; Ying Zhu; Lining Yang; Ruonan Bai; Qianyi Rao; Qiang Zhang; Di Wu; Feng Wang; Qinghua Zhao; Mingzhao Xiao (Frontiers Media S.A., 2022)
ObjectiveSocial participation has become a policy framework to address population aging. However, little is known about the social participation of older adults in western China, and extensive, multicenter, regional research is lacking. This research investigated the profiles of social participation of older adults in western China and explored the characteristics and factors influencing social participation.MethodThis cross-sectional study was conducted in 3 provinces (Chongqing, Sichuan, and Inner Mongolia) in western China from March 2021 to December 2021 and included 3,456 participants aged 60 years or older. Social participation was assessed using the Chinese version of the Impact on Participation and Autonomy Questionnaire (IPA). Latent profile analysis (LPA) was performed to extract latent classes of social participation among older adults in western China. The chi-square test and multinomial regression analyses were used to identify differences between these classes.ResultsThree social participation classes were identified by LPA: high social participation (25.2%), moderate social participation (55.1%), and low social participation (19.7%). Being older, having a primary school education level, having mobility or speaking impairment, using assistive devices, and having a chronic disease were highly associated with the low social participation class (P < 0.05). Furthermore, older adults with no dependence (OR = 0.018, 95% CI = 0.005-0.062) or mild dependence (OR = 0.039, 95% CI = 0.011-0.139) in activities of daily living (ADLs) were less likely to be in the low social participation class. Older adults who were cared for by non-spouse primary caregivers were more likely to be assigned to the moderate social participation group (OR = 2.097, 95% CI = 1.501-2.930) than to the high social participation group.ConclusionsMost older adults in western China have a moderate level of social participation. Advanced age, reduced ADL ability, reduced speech ability, reduced mobility, and non-spouse care are related to the level of social participation. Healthcare professionals should pay attention to the predictors for different classes, identifying high-risk groups as early as possible.